Digital medicine : health care in the Internet era - West, Darrell M., 1954- (Brookings Institution Press, 2009)
"Investigates factors limiting the ability of digital technology to remake health care. Analyzes data sources to study content of health care-related websites, sponsorship status, public usage, and the relationship between e-health use and health care attitudes. Examines the different ways in which officials overseas have implemented health information technology"--Provided by publisher